ANALISA LITERASI KEUANGAN, INKLUSI KEUANGAN DAN KINERJA USAHA UKM PETANI BUNGA KOPENG - Wachidah Fauziyanti; Fidyah Yuli Ernawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract. The purpose of this study was to determine the understanding of financial literacy and inclusion as well as the business performance of respondents who are members of cooperatives in Kopeng village. Data obtained by survey through a questionnaire given to 37 respondents. While the research method used is descriptive qualitative research. Where the survey results obtained the category index of financial literacy, financial inclusion and the performance of the respondent's business. The results of financial literacy were obtained by an average of 3.85 or a sufficient literate category scale with a percentage of more than 75% understanding, financial inclusion was obtained by an average of 3.71 or sufficient category financial inclusion because the respondents on average had access to banks and institutions financing, while the respondent's business performance obtained an average of 3.86. Suggestions for respondents to further improve financial literacy and inclusion which are expected to have an impact on improving business performance. For further research, a quantitative research method can be used, the effect of the three variables and other research objects.